Asymmetric synthesis of (1R, 2S)-1-amino-2-vinylcyclopropanecarboxylic acid by sequential SN2–SN2′ dialkylation of (R)-N-(benzyl)proline-derived glycine Schiff base Ni(ii) complex. Issue 2 (1st December 2014) - Kawashima, Aki; Xie, Chen; Mei, Haibo; Takeda, Ryosuke; Kawamura, Akie; Sato, Tatsunori; Moriwaki, Hiroki; Izawa, Kunisuke; Han, Jianlin; Aceña, José Luis; Soloshonok, Vadim A.
Abstract : The synthesis of the title compound, a key structural fragment of several hepatitis C virus inhibitors, is described. Abstract : This work describes a new process for the asymmetric synthesis of (1 R, 2 S )-1-amino-2-vinylcyclopropanecarboxylic acid of high pharmaceutical importance. The sequence of the reactions includes PTC alkylation (SN 2), homogeneous SN 2′ cyclization followed by disassembly of the resultant Ni(ii ) complex. All reactions are conducted under operationally convenient conditions and suitably scaled up to 6 g of the starting Ni(ii ) complex.